Comparação do controle postural de meninas adolescentes com e sem sintomas de asma - (:unkn) unknown (Universidade Federal do Pampa, 2020)
OBJECTIVE: To compare the postural control of adolescent girls with and without asthma symptoms, students of a public school, in a municipality of Fronteira Oeste do Rio Grande do Sul, Brazil. METHODS: The girls were selected through the ISAAC questionnaire (International Study of Asthma and Allergies in Childhood), which aims to show the prevalence of symptoms of asthma, allergies and rhinitis. It consists of 8 questions regarding signs and symptoms and the last one about diagnosis, when reaching a score of 5, the individual can be considered as having asthma symptoms. Postural control was evaluated using dynamic computerized posturography, using Sensory Organization Tests (TOS), divided into six sensory conditions. RESULTS: Twenty 10-year-old girls participated in the study, 10 from the control group (CG) and 10 children with asthma symptoms (GA). It is possible to observe that in both groups, overweight (overweight + obesity) was present in most of the evaluated women. Girls with asthma symptoms showed worse balance in TOS condition II (P = 0.048), when compared to the asymptomatic group, thus showing a greater deficit in the proprioceptive and vestibular system. CONCLUSION: Adolescent girls with asthma symptoms have a deficit in postural control, especially in the proprioceptive and vestibular systems.
Comparison of postural control of adolescent girls with and without asthma symptoms
Keywords: Controle postural; Meninas; Adolescentes; Asma; Escolares; Postural control; Girls; Adolescents; Asthma; Schoolgirl; Fisioterapia; Physiotherapy; CNPQ::CIENCIAS DA SAUDE